Atividade, cotidiano e ocupação na terapia ocupacional no Brasil: usos e conceitos em disputa - Poellnitz, Jéssica Cristina Von (2018)
The present work aims to analyze the adoption and concepts of the terms activity, occupation and day-to-day in occupational therapy in Brazil. To accomplish its objective, this work was composed of two phases to collect and analyze the data: 1) historical mapping of the use of terms in a national occupational therapy conference; 2) the usage of the terms by occupational therapists in the country currently. The first phase consisted of a theoretical investigation of the theme and mapping the adoption of the terms in the Brazilian Congress of Occupational Therapy (CBTO), between the years of 1989 and 2015. The second phase consisted of conducting interviews with five occupational therapists who perform and/or accomplished important discussions and/or publish (in journals and/or books and/or scientific conferences of the field) about the theme addressed in this study. The results of the first phase are organized textually and graphically in order to present the historical progress of the employment of the terms in the occupational therapy in Brazil and, more specifically, in the CBTO. From these results it was possible to detect the predominant usage of the term activity in the development of the history of the profession and its variations of the lexical field, as well as the increase of the adoption of the term day-to-day starting on the year of 2003 and the term occupation starting on the year of 2007. The data obtained from the second phase were analyzed and organized in theme categories: a) understanding of the employment of terms by occupational therapists – composition between private and plural; b) individual-aggregate perceptions – the application of the terms in occupational therapy and critical issues involved; c) training in occupational therapy. These results allow us to affirm that four main categories influence the adoption of a term and its conceptual body: identity, trajectory, conceptual perspective and experience. Therefore, several aspects affect the usage of the words and its concepts becomes subjective and unique. In addition, activity is the expression most adopted among the interviewed occupational therapists, followed by day-to-day. Only one interviewee uses the term occupation, such term that had different criticisms and controversial arguments pointed out by the interviewed professionals. Regarding training in occupational therapy, it was concluded that this theme is fundamental, although, as the interviewees mentioned, it is taught in different ways in the several higher education institutions in the country, which is worrisome, resulting in greatly contrasting formations based on the foundation content for the profession. Finally, we entice the need for investment in reflections that concern production of knowledge about the subject, considering that the interviewees pointed out that this remains precarious. We emphasize that the present research consists of only a part of the game of forces, of dispute and power intrinsic to the field of knowledge, in which it is necessary to consider many other components to deepen the questions concerning the epistemological foundation/conceptualization in occupational therapy.